Implikasi Sistem Pendukung Manajemen Terhadap Lingkungan Organisasi. - Perpustakaan UGM, i-lib ([Yogyakarta] : Fakultas Kehutanan Universitas Gajah Mada, 1999)
ABSTRAK Computer applications for management support are on the rise. The microcomputer revolution made computer available on many managers' desks. Managers may now access thousands of databases and computerized analysis in their decision making. Corporate are developing distributed systems that enable easy accessibility to data stored in multiple locations. Various information systems are being integrated with each other and/or with other automated systems. Managers can make better decisions because they have more accurate information at their fingertips. Decision Support Systems, Group Decisions Support Systems, Executive Information Systems, Expert Systems, and Artificial Neural Networks, collectively called Management Support Systems (MSS), are the major technologies behind this developments. Introduction of MSS may create a significant change in organization and this article discusses the implications of implementing MSS in organizations. Key word: Manajement Support Systems, Network, Rekayasa ulang